The effect of glucose tolerance test on fetoplacental circulation - Gültekin Adanaş Aydın; Pınar Özdemir Akdur; Gülten Özgen (Elsevier, 2021)
Objective: Acute hyperglycemia affects the fetoplacental circulation. This study aims to investigate the possible effect of acute hyperglycemia induced by 50 g oral glucose tolerance test (OGTT) on fetoplacental circulation in women between 24 and 28 weeks of gestation. Materials and methods: Between January 2019 and April 2019, a total of 29 women who were between 24 and 28 weeks of gestation with a singleton gestation and were in low-risk group were included in this prospective study. All patients underwent fetal biometric measurements using ultrasonography (USG) and were administered 50 g OGTT. Before and 1 h after the test, Doppler USG was used to measure uterine artery, umbilical artery (UA), middle cerebral artery (MCA), pulsatility index (PI), resistance index (RI), and systolic/diastolic (S/D) ratio. The cerebroplacental ratio (CPR) was calculated as the ratio of the MCA-PI/UA-PI. Results: There was a decline in the MCA-RI (p = 0.008) and UA-PI (p = 0.021) at 1 h after the administration of 50 g OGTT. Z-scores of the mean UA-PI, MCA-PI, and CPR were calculated and a statistically significant increase in the Z-scores of the mean UA-PI was observed (p = 0.028). Conclusion: Our study results show that acute hyperglycemia induced by OGTT significantly increases the Z-scores of the UA-PI, affecting the fetoplacental circulation.